The effect of sintering temperature on microstructure and mechanical properties of alloys produced by using hot isostatic pressing method - Yildiz, Tulay; Kati, Nida; Gur, Ali Kaya (Elsevier Science Sa, 2018)
In this study, a new matrix material was produced via HIP (Hot Isostatic Pressing) method by adding Cobalt and Nikel elements to CuSn (85/15) bronze alloy at certain ratios and the effect of sintering temperature during the production was examined. One of the biggest advantages of the HIP method is that the heat and pressure are applied at the same time during sintering process. Thus, all or almost all of the gaps during the production were removed and a more dense material was obtained. During the operation, it was kept constant that the sintering pressure was 30 MPa and the sintering time was 15 min, and the sintering temperature was selected as the variable parameter between 700 degrees C and 800 degrees C. The sintering process was carried out under the vacuum condition after the moment of first combustion. The produced samples were then metallographically prepared and SEM and EDS analyses were carried out for microstructure studies. Microhardness was taken from the samples and three-point bending test was carried out in order to examine the mechanical behaviors of the samples. Finally the density test was applied to the samples and their experimental and theoretical densities were calculated. As a result, it was observed that more homogeneous samples were obtained by increasing the sintering temperature. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: HIP (Hot Isostatic Pressing); Powder metallurgy; Microhardness Three-point bending; Density; CuSn; Co; Ni